EVALUATION OF DOCUMENTATION SEQUENCE CAUSES PERINATAL - Widyaningrum, Linda; Sugianto, Zaenal; Setiawan, Bagas (LPPM Universitas Duta Bangsa Surakarta, 2023)
The Underlying cause of death is an event or condition without which the patient would not have died. The aim of the research is to determine the accuracy of writing the sequence of causes of perinatal death based on mortality rules The research method used in this research is descriptive research, with a retrospective approach. Data collection using observation and interviews. The research population was 50 medical record documents of patients who died perinatally in 2018-2022 using a saturated sampling technique. The percentage of accuracy in writing the sequence of perinatal deaths at PKU Muhammadiyah Hospital Surakarta shows 100% inaccurate. The writing inaccuracy is due to the writing not being in accordance with the existing standart Operating Procedure, the order of perinatal death is still written on the medical certificate for the cause of adult death. The accuracy of writing the order of perinatal deaths is still relatively low. It would be better if the hospital further increases its outreach activities so that medical personnel can write the order of death on the certificate correctly in accordance with the rules or standards that apply in the hospital.